An overview of the multi-dimensional mechanisms of exercise-regulated hormones and growth factors in cardiac physiological adaptation - Huang, Shuaiwang; Chen, Zhanglin; Li, Haoming; Zheng, Lan; Zhou, Zuoqiong; Peng, Xiyang; Tang, Changfa (Frontiers in Physiology, 2025)
Physiological cardiac hypertrophy represents an adaptive response of the heart to chronic physiological stimuli, including sustained exercise, and is characterized by cardiomyocyte enlargement and structural optimization to enhance pumping efficiency. While several studies on cardiac physiological adaptation have been published recently, a systematic integration of information on exercise-regulated hormonal and growth factor networks remains lacking. To address this limitation, toward the systematization of a ‘multi-dimensional mechanism’ model, here we review the molecular mechanisms underlying exercise-induced physiological cardiac hypertrophy, with particular focus on how physical activity regulates hormones and growth factors including insulin-like growth factor-1, vascular endothelial growth factor, neuregulin-1, and norepinephrine. These mediators activate intricate signaling pathway networks that promote protein synthesis in cardiomyocytes, strengthen myocardial contractility, and induce angiogenesis. The highlighted findings not only provide novel insights into the cardioprotective mechanisms of exercise but also identify potential biomarkers that enable the development of precision exercise prescriptions tailored to individuals with cardiovascular diseases.